2018
DOI: 10.13057/biodiv/d190332
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seed morpho-physiological and biochemical traits of Java olive populations originated from Java, Bali, Lombok, and Timor Islands, Indonesia

Abstract: Sudrajat DJ, Suwandhi I, Siregar IZ, Siregar UJ. 2018. Variation in seed morpho-physiological and biochemical traits of Java olive populations originated from Java, Bali, Lombok, and Timor Islands, Indonesia. Biodiversitas 19: 1004-1012. Java olive (Sterculia foetida L.) is one of the promising non-edible feedstocks for biodiesel production. Utilization of this tree species for plantation is limited due to knowledge gaps in many fundamental aspects of seed properties. The aim of the study was to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Annicchiarico et al (2010) suggested that to predict superior genotype, considerations of heritability must be combined with genetic gains in the tested traits. High heritability coupled with high genetic gains indicated the additive gene effects, whereas high heritability coupled with low genetic gains indicated non-additive gene effects (Atnaf et al 2017;Nehe et al 2019;Sudrajat et al 2018). The yield had high heritability and genetic gains in the mutant population, but the cross-bred population had moderate heritability and low genetic gains.…”
Section: Discussionmentioning
confidence: 99%
“…Annicchiarico et al (2010) suggested that to predict superior genotype, considerations of heritability must be combined with genetic gains in the tested traits. High heritability coupled with high genetic gains indicated the additive gene effects, whereas high heritability coupled with low genetic gains indicated non-additive gene effects (Atnaf et al 2017;Nehe et al 2019;Sudrajat et al 2018). The yield had high heritability and genetic gains in the mutant population, but the cross-bred population had moderate heritability and low genetic gains.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the diversity of seed germination capacity between provenances was very high, ranging from 53.5% to 82.8%. High variability in germination between populations was also reported in Nothofagus glauca (Moya et al 2017) and Sterculia foetida (Sudrajat et al 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Germination capacity before and after storage was quite varied between provenances. Diversity of seed germination and storability among provenances were also reported in Swertia chirayita (Pradhan and Badola 2012) and S. foetida (Sudrajat et al 2018). Seed germination after storage for 5 years was significantly negatively correlated with initial seed moisture content (r 2 = -0.933).…”
Section: Discussionmentioning
confidence: 57%
“…Differences in fruit, seed and seed germination characteristics of N. orientalis were also reported by [22] by examining its four natural habitats, i.e., swamps, temporal swamps, dry land, and temporal swamp savanna. Several studies have reported that differences in the morphophysiological characteristics of fruit and seeds from different population or provenance are strongly influenced by genetic factors [18,23,24,25]. Differences in mother tree of N. orientalis also affect the growth of seedlings in nurseries [26].…”
Section: Variation Of Mother Trees and Seed Characteristicsmentioning
confidence: 99%